Give my regrets to Broadway : from the tattered casebook of Chet Gecko, private eye - Hale, Bruce (Orlando, Fla. : Harcourt, 2004)
Chet and his partner, Natalie Attired, take on a case involving an actor gone missing from the school musical.
560
Accelerated Reader AR
Keywords: Geckos -- Juvenile fiction; Drama -- Juvenile fiction; Schools -- Juvenile fiction; Animals -- Juvenile fiction; Geckos -- Fiction; Theater -- Fiction; Schools -- Fiction; Animals -- Fiction; Humorous stories; Mystery fiction